Biomehanični model človeškega kolena pri aktivnem obremenjevanju - Kranjec, Matej (visokošolska dela, 2020)
The goal of this thesis is the development of a biomechanical model of the human knee for use in numerical simulations with the option of muscle activation. For an accurate stress-strain response of the model, we need accurate mechanical properties of the knee ligaments and function of muscle activation. We want to gather mechanical properties of the patellar ligament by means of tensile testing in simulated physiological conditions and measure the muscle activation response using the MC sensors in isokinetic measurements. The results of the patellar ligament tensile response are in the scope of other research findings. The MC sensor response does not represent isolated muscle activity. We have developed the active knee model that continues to evolve.
Keywords: aktivacija mišic; biomehanični model; Disertacije; dissertations; finite element; knee; Koleno; končni elementi; lower extremity; muscle activation; numerical model; Numerični modeli; patelarni ligament; patellar ligament; spodnje okončine